Arctic and tundra soils on the new digital soil map of Russia, 1 : 2.5 M scale - T. V. Ananko; M. I. Gerasimova; D. E. Konyushkov (Бюллетень Почвенного института им. В.В. Докучаева)
V.V. Dokuchaev Soil Science Institute has initiated a project on compilation of a new Digital Soil Map of Russia on the basis of the Soil Map of the Russian Federation (SMRF) 1 : 2.5 M scale (1988) revised and interpreted in ideology and nomenclature of the new substantive-genetic Classification System of Russian Soils (CSRS). The first stage implies the conversion of soil mapping units on the original map into the CSRS with a corresponding renaming of soils in the attribute database to the digitized version of the map for each soil polygon. During the second stage, a new digital model of the soil cover is developed with the use of digital soil mapping technologies, basic soil map, and new materials, including satellite images and digital elevation models. The legend section “Tundra Soils” contains 16 soil units forming their own areas or found in various combinations (soil complexes). As a result of the reclassification and careful analysis of each soil polygon, the soils of Arctic and Subarctic tundra have obtained a more detailed and differential representation on the new map, and their diagnostics based on the morphology of the profiles and major soil properties have been specified. The most significant changes in the initial content of the map concern the soils referred to as gley soils on the SMRF. A separate group of cryozemic soils has been specified. Weakly developed soils (petrozems, psammozems, and pelozems) and lithozems have been introduced on the map for the first time. Differential decisions are suggested for the soils of “spotty tundra” with sorted and nonsorted circles and for the soils of cryogenic fissures and cracks. The results of the study have made it possible to refine the diagnostics and nomenclature of soils in the CSRS.